What is going wrong in health research investment? post-pandemic lessons and the need for change (Journal of Ideas in Health, 2020)
The emergence of a new dimension of consciousness after the COVID-19 pandemic might provide an opportunity to highlight gaps and inequalities in health research investment and to mobilize scientific and public opinion to change the way things are done. This analysis considers some lessons learned from the pandemic crisis concerning the priority of global health research, research in prevention and well-being, and international research cooperation. The question raised by these issues concerns the unfairness of health research funding, mainly dominated by the pharmaceutical and device industries. However, evidence shows that these companies shifted funding to late-phase clinical trials and away from innovation activity and global health priorities. On the other hand, public institutions continue to invest in basic science, with the majority of funds still focused on basic research and innovation. This direct relationship between industry and biomedical research disrupts the reliability of findings and biases the evidence. Several initiatives and efforts are shaping pathways towards health research independence from industry funding. We can propose the idea of industry funding without a direct relationship with researchers through a common pot managed by an independent international agency. Nevertheless, to promote publicly funded research, the scientific community must strengthen its position compared to industry-funded research through transparency and the scientific value of publications.
Keywords: COVID-19, Post-pandemic, Lessons, Tunisia